A note on epistemic and effective meanings of the Polish perfective and imperfective - Kochańska, Agata (Vilnius University Open Series, 2021)
The paper offers an analysis of selected uses of the Polish perfective and imperfective in the non-past indicative and in the imperative construction. In uses under consideration, both the perfective and the imperfective refer to a single complete occurrence of a telic process and, hence, the semantic contrast between them is not a matter of distinctions such as boundedness/unboundedness, completion/non-completion, telicity/atelicity, punctuality/durativity, etc. The paper presents a qualitative analysis of selected corpus examples which is aimed at elucidating the nature of the relevant contrast. The claim advocated in the course of the discussion is that the perfective/imperfective contrast may play a role in the system of clausal grounding in Polish, as it may convey the idea of, respectively, epistemic and/or effective non-immediacy/immediacy of the profiled process relative to the ground.
Keywords: verbal aspect; Polish; clausal grounding; non-past indicative; imperative